Racial "Othering" in Thailand: Quantitative Evidence, Causes, and Consequences. Issue 3 (3rd July 2019) - Draper, John; Sobieszczyk, Teresa; Crumpton, Charles David; Lefferts, H. L.; Chachavalpongpun, Pavin
Abstract: This article quantitatively investigates racial "othering" in Thailand by using available World Values Survey proxies. We review racial "othering" in Thailand through inter-group threat theory. We investigate the proportion of Thais who are racially and/or ethnically prejudiced, the number of Thais who are racially and/or ethnically prejudiced compared with other countries' citizens, whether Thais have become more racially and/or ethnically prejudiced from 2007 to 2013, the extent to which Thais are religiously discriminatory compared with other countries' citizens, and whether Thais became more religiously discriminatory from 2007 to 2013. We find relatively high levels of racial prejudice by Thais.